PENGARUH SENAM ZUMBA TERHADAP PENINGKATAN KEKUATAN OTOT PERUT PADA WANITA YANG PERNAH MELAHIRKAN DI DUSUN SANGLAH UTARA - I Gusti Ayu Rea Vera Wijaya; A.A Nyoman Trisna Narta Dewi; Susy Purnawati (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Abdominal muscle strength decreasing could happen in women who has been giving birth. Zumba exercise is a modification of aerobic exercise with latin music and dance that could be used for muscle strengthening exercise. The purpose of the experiment is for knowing the effect of zumba exercise to increase the abdominal muscles strength in women who has been giving birth. The research is a pre-experimental with a pre-test and post-test one group design. The research has been done in North Sanglah Village with total of 18 samples that was chosen by the Curl Up test score and inclusion and exclusion criteria. Data analyzed using Saphiro Wilk test and Wilcoxon Test. The results shown there are significant increasing of abdominal muscles strength after given the zumba exercise, p=0,000 (p<0,05). Zumba exercise could increase the abdominal muscles strength in samples with a 26,7% increasing percentage. Keywords: zumba exercise, abdominal mucles strength decreasing.